1960
DOI: 10.2514/8.5020
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Liquid PropelIant Rocket Combustion Instability and Its Experimental Verification

Abstract: A straightforward theoretical formulation of the longitudinal high frequency rocket stability criteria is presented. Based on Crocco's sensitive combustion time lag theory, the derivation ii considerably simpler, although somewhat less rigorous, than previously published detailed treatments. A series of rocket motor experiments is described, demonstrating that there exists ar upper limit to the chamber length at which each mode of longitudinal high frequency pressure oscillations will occur, and that this limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1962
1962
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…This has been a reasonably successful approach for liquid rockets (Ref. 25, for example,) principally, it seems, because the time lag is at most a very slow function of frequency; the dependence on combustion parameters (fuel/oxidizer ratio particularly) may be inferred from observation of the stability boundary. This happens to be a fortunate situation, since there exists no way of computing 'T for a liquid rocket.…”
Section: Jt-tmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been a reasonably successful approach for liquid rockets (Ref. 25, for example,) principally, it seems, because the time lag is at most a very slow function of frequency; the dependence on combustion parameters (fuel/oxidizer ratio particularly) may be inferred from observation of the stability boundary. This happens to be a fortunate situation, since there exists no way of computing 'T for a liquid rocket.…”
Section: Jt-tmentioning
confidence: 99%
“…Usually, an Arrhenius law has been assumed for the conversion of solid to gas, giving the total surface mass flux (25) In most cases, the dependence on pressure has been ignored (ns = 0). A general perturbed form of (25), to first order of small quantities, is (26) with E = Es/RoTs the dimensionless activation energy for the surface reaction.…”
Section: Solid-gas Interfacial Regionmentioning
confidence: 99%
“…The third form of instability is the excitation of the acoustic vibrational modes of the combustion chamber (pressure mode). While these modes may act individually or in concert, both Markstein, 1964 andCrocco et al, 1960 noted that for flames enclosed in a duct, the pressure mode exhibits the dominant disturbance and can be the most destructive. Thus the pressure mode is the primary focus of this research study, however consideration is also given to the vorticity mode as a mechanism for variations in the heat release.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A considerable amount of research, both experimental and theoretical, has been performed in the area of combustion dynamics on these devices and from these studies, three general classifications of combustion instabilities have been identified (Crocco et al, 1960 andMarkstein, 1964). First, low-frequency oscillation due to the geometry of the combustion chamber and propellant feed system (shear mode).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By neglecting the effects of the liquid phase in the momentum equation written for the gas phase (a similar simplification also has been used in more recent work by Crocc0 9 ) and by emphasizing the energy additions, one may deduce a single equation for pressure fluctuations. This differential equation then can be converted to an integral equation that may be solved approximately by a known perturbation-iteration technique.…”
Section: Introductionmentioning
confidence: 99%